Talking the Talk, Moral Entrapment, Creeping Commitment? Exploring Narrative Dynamics in Corporate Responsibility Standardization - Haack, Patrick; Schoeneborn, Dennis; Wickert, Christopher (Organization studies, 2012)
This paper examines the type and temporal development of language in the process of corporate responsibility (CR) standardization. Previous research on CR standardization has addressed the proliferation and organizational embedding of material practices but neglected the analysis of underlying ideational dynamics. Departing from this practice, we introduce a narrative perspective that illuminates the trajectory a CR standard follows, from being formally adopted to becoming collectively accepted as a valid solution to a problem of societal concern. We argue that this perspective helps scholars explore the dynamic interplay between symbolic and material aspects of standardization and understand better the discursive antecedents of coupling processes in organizations. Drawing on the case of the Equator Principles standard in international project finance, we empirically study how narratives create meaning shared by both business firms and their societal observers, thereby exemplifying the analytical merit of a narrative approach to CR standardization.